Communication and Calibraton of Sensing Meters - Harrouz Abdelkader; Omar Harrouz; Ali Benatiallah (Institute of Advanced Engineering and Science, 2014)
The purpose of this paper is to review the essential definitions, roles and characteristics of communication on metering system. We discuss measurement, data acquisition and metrological control of a signal sensor from dynamic metering system. After that, we present instruments of sensor communication with more detailed discussions to the reference standards and the important fundamental parameters to consider when designing a dynamic communication metering system. We finished with control and calibration of turbine flow meter and we given resultats expermentaly of this work.